2010
DOI: 10.5539/ass.v6n9p12
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Community Participation Levels in Community-based Health Programs Regarding Breast Cancer Prevention in Metropolitan Tehran, Iran

Abstract: Iran has recognized community participation in health research as an essential part of the country's health system. Community participation is focused on the prevention of communicable diseases, mother and child care, family planning and first aid. Besides, the issues of health education and community participation regarding breast cancer prevention are not similar to other activities included into primary health care services, such as family planning in Iran. Within this context, increasing the participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The two versions (Persian and English) of the questionnaire were reviewed by a group of experts in breast cancer screening and arrangement was achieved over the translation. More information of the psychometric assets of the scale and the instrument have been lately published elsewhere ( Ahmadian et al , 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two versions (Persian and English) of the questionnaire were reviewed by a group of experts in breast cancer screening and arrangement was achieved over the translation. More information of the psychometric assets of the scale and the instrument have been lately published elsewhere ( Ahmadian et al , 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, these are community- focused programs prepared for health promotion, especially breast cancer prevention along with family planning, maternal health, children vaccination and prenatal care, and other community health programs in Iran. More details related to women’s participation in breast cancer prevention programs in Iran have been recently published elsewhere ( Ahmadian et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asian cultures express conservative attitudes towards women's bodily experiences and exposure. Previous studies have highlighted that women were hesitant or reluctant to breast cancer screening as it requires their bodies to be touched by the health care providers, especially male health care providers (Abdullah et al, 2011;M. Ahmadian, 2011;Parsa, Kandiah, Abdul Rahman, & Zulkefli, 2006).…”
Section: Perceived Barriers To Breast Cancer Screeningmentioning
confidence: 99%
“…Meanwhile, Ahmadian, Redzuan, Emby & Samah (2010) stated that the current study presented the levels of community participation in community based program about breast cancer by women who have participated in mammography. Based on the findings of this study it can be concluded that, levels of women community participation are limited.…”
Section: Factors Affecting Performance Of Posdayamentioning
confidence: 99%
“…To date, a comprehensive evaluation of Iranian women community participation and breast cancer prevention has not been undertaken. Finding will be useful, for this at risk population (women) with emphasis on their role in their own health development and its sustainability (Ahmadian, Redzuan, Emby, & Samah, 2010).…”
Section: Factors Affecting Performance Of Posdayamentioning
confidence: 99%